THE DOUBLE SERPENT: POLITICAL AND ECONOMIC POWER IN THE FORMATION OF CAPITALISM. - Cerdas Vega, Gerardo (2013)
This paper analyzes the historical links between political and economic power in the formation of capitalism, from the standpoint of long-time periods and the role that power had in shaping the economy and society in Europe since the sixteenth century. The result of this process is an capitalist interstate system whose expansive dynamic reached the entire globe and whose entanglement we need to solve in order to overcome naturalized readings on the formative process of global economic and political order.